Faktor-Faktor Yang Mempengaruhi Kinerja Guru di SMP Negeri 4 Abiansemal - Swandewi, Ni Putu Yuni Diah; Ayu Wimba, I Gusti; Wijaya, Putu Yudy (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Teacher performance can be understood as the workability of teachers in carrying out their main duties as educators. Teacher professionalism is one of the benchmarks for the inevitability of quality education. Analyzing the factors that influence teacher performance, especially at SMP Negeri 4 Abiansemal is the main objective of this study. This exploratory descriptive study consists of three variables, namely internal factors, external factors, and performance. The object of this study is teacher performance which is influenced by internal and external factors. The population in this study were all civil servants teachers at SMP Negeri 4 Abiansemal, totaling 32 people. The sample used was comprehensive because the population did not reach 100. The data collection methods used were questionnaires and documentation. The data analysis technique used multiple linear regression. The study showed that (1) The factors that influence teacher performance are internal factors consisting of abilities, needs, interests, expectations, and beliefs, and external factors consisting of situational and environmental factors. (2) The dominant factor influencing teacher performance at SMP Negeri 4 Abiansemal is the external factor because the internal factor is included in group 1 with a value of 0.824.